The Trope Tank: A Laboratory with Material Resources for Creative Computing - Nick Montfort; Erik Stayton; Natalia Fedorova (Texto Digital)
Principles for organizing and making use of a laboratory with material computing resources are articulated. This laboratory, the Trope Tank, is a facility for teaching, research, and creative collaboration and offers hardware (in working condition and set up for use) from the 1970s, 1980s, and 1990s, including videogame systems, home computers, and an arcade cabinet. To aid in investigating the material history of texts, the lab has a small 19th century letterpress, a typewriter, a print terminal, and dot-matrix printers. Other resources include controllers, peripherals, manuals, books, and software on physical media. These resources are used for teaching, loaned for local exhibitions and presentations, and accessed by researchers and artists. The space is primarily a laboratory (rather than a library, studio, or museum), so materials are organized by platform and intended use. Textual information about the historical contexts of the available systems, and resources are set up to allow easy operation, and even casual use, by researchers, teachers, students, and artists.